Indonesia and the ASEAN-China Free Trade Area : why Indonesia did not prepare properly for the full implementation of ACFTA in 2010? - Riezqia, Shiela. (2013)
The full implementation of the ASEAN-China Free Trade Area has come into effect since January 2010 but Indonesia does not gain significant benefits from it. Its industries suffer from production and profit decline as well as from termination of employment. Based on the author's study, the problem appears because the country did not have a strategy to face the ACFTA even though the government had 9 years to create one. This paper investigates why Indonesia did not prepare properly for the ACFTA full implementation. It first reviews the ASEAN-China Free Trade Area and Indonesia's experience within the ACFTA briefly. Then it will analyze the reasons behind Indonesian government's lack of preparation. Moreover, it will compare Malaysia, Thailand and the Philippines’ experiences within the ACFTA to explain the importance of a strategy, a good coordination and an effective communication among the stakeholders or the related institutions to create a strategy. In the last chapter, the paper comes to the conclusion that the Indonesian government and ministries did not prepare properly to create a strategy because of their ignorance and lack of good coordination, the ministers' difference of ideas, nature and positions, and an ineffective communication from the central government to the business communities and to the parliament. In the end, the author also provides some policy recommendations and expected results from them.